Adult Education at the Ta'lim Assembly at the An-Nuur Mosque - Lutfi Wahyuningrum (Fahmina: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of adult education at the Ta'lim Council at the An-Nour Mosque, Ward VIII Dalan Lidang, which includes educational objectives, characteristics of educators and students, learning materials, methods, and media used in the learning process. This study uses a qualitative approach with the type of field research. Data was collected through observation, in-depth interviews with administrators, ustaz/ustazah, and ta'lim assembly congregations, and documentation studies. Data analysis is carried out descriptively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that adult education at the Ta'lim Council of the An-Nuur Mosque is directed to increase understanding of Islam, strengthen worship practices, foster morals, and strengthen social relations between worshippers. The educators involved have adequate religious competence and experience in da'wah activities and community learning. Students are dominated by adults with diverse educational, occupational, and religious backgrounds. The learning materials include faith, worship, morals, interpretation of the Qur'an, hadith, and various religious issues relevant to the needs of the congregation. The learning methods used include lectures, discussions, questions and answers, and worship practices, while learning media utilizes Islamic books, the Qur'an, audio devices, and simple presentation media. This study concludes that the Ta'lim Council of the An-Nuur Mosque, Ward VIII Dalan Lidang has carried out the function of adult education effectively through the implementation of learning in accordance with the needs of the congregation, thereby contributing to increasing religious literacy, forming Islamic character, and strengthening the social cohesion of the community.